Akad in Digital Business: A Study of Fiqh Muamalah on Marketplace and E-Commerce - Muhammad Tang; Nilfatri Nilfatri (Zabags Qu Publish, 2024)
The development of digital technology has driven a major transformation in the business world, particularly through the emergence of marketplaces and e-commerce. This situation creates the need to reexamine the concept of contracts (akad) in Fiqh Muamalah so that they can be applied relevantly in the digital context. This article aims to examine the types of contracts that occur in marketplace and e-commerce practices and their conformity with Sharia principles. The research method used is library research by analyzing classical and contemporary literature on contracts, as well as fatwas from modern Islamic financial institutions. The study's findings show that digital transaction practices can be categorized into several types of contracts, such as bai’ (sale), wakalah (agency), and ju’alah (reward-based service), each of which can be adapted to Islamic legal provisions. By fulfilling the pillars and conditions of the contract and avoiding elements of uncertainty (gharar) and interest (riba), digital transactions in e-commerce can be categorized as valid according to Islamic law